2017
DOI: 10.2298/vsp151110246t
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with early childhood caries in autonomous province of Vojvodina, Republic of Serbia

Abstract: Background/Aim. Early childhood caries (ECC) is still unexplored in Vojvodina an autonomous province of the Republic of Serbia. The aim of this study was to determine its prevalence in preschoolers and to define the risk factors that affect the prevalence of this disease. Methods. The survey was designed as a cross-sectional analytical study of preschool children in the region of Vojvodina, the Republic of Serbia. Sample type has been projected as a systematic sample and contained both parents and their childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Multiple researches have been emphasized the association between parental knowledge and development of ECC. 8,9 Hashim et al 13 reported that parent's education, especially the mother's educational level, was associated with ECCthe higher the education, the lower the prevalence. 8 Putting prevention as the main focus, in order to decrease the risk factors for ECC development, it is essential to establish partnerships with the children's family members so they can be informed and educated with the issues at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple researches have been emphasized the association between parental knowledge and development of ECC. 8,9 Hashim et al 13 reported that parent's education, especially the mother's educational level, was associated with ECCthe higher the education, the lower the prevalence. 8 Putting prevention as the main focus, in order to decrease the risk factors for ECC development, it is essential to establish partnerships with the children's family members so they can be informed and educated with the issues at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple researches have been emphasized the association between parental knowledge and development of ECC. 8,9 Hashim et al reported that parent's education, especially the mother's educational level, was associated with ECCthe higher the education, the lower the prevalence. 8,13 Putting prevention as the main focus, in order to decrease the risk factors for ECC development, it is essential to establish partnerships with the children's family members so they can be informed and educated with the issues at hand.…”
Section: Discussionmentioning
confidence: 99%
“…1 Low parental knowledge could be one of the reasons for more prevalence of ECC which can be prevented by creating awareness among people. 8,9 This can be done by conducting awareness programs. These programs can produce positive changes or prevent negative changes in health-related behaviours among large population group.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the data from Tušek and colleagues, who showed that the prevalence of caries in Vojvodina was 46.64%, while in the children who were involved in this study it was 62.4%. [15] also significantly increase the possibility of caries in a permanent dentition [17,18]. Early childhood caries is a disease for which treatment is not just a restorative treatment.…”
Section: Discussionmentioning
confidence: 99%